SECONDARY BENDING ANALYSIS OF AIRPLANE TYPICAL SINGLE-SHEAR LAP JOINT - YANG Jing; JIANG XingChang; WANG HuiMei (Jixie qiangdu)
As an important structural component of a plane in its fatigue design,typical single-shear lap joint usually requires the analysis of its secondary bending. With the flat shells, by rational modelestablishing and analysis, the papergot the secondary bending of all fatigue detail points. At the same time, the paper validated the flat shells method. The calculation results and conclusionspresented in the paper are of reference value for the fatigue design of airplane’s typical single-shear lap jointstructures.